Perspective of specialist nurses on atraumatic care in pediatrics - Carvalhais,Maribel (2022)
Abstract Introduction: Hospitalization consists of a health-disease transition which enhances negative effects on child and family, such as changes in family dynamics, setbacks in development, anxiety and fear. The provision of atraumatic care should be a basic premise in Pediatrics to minimize these effects. Objective: Identifying the knowledge of Specialist Nurses about atraumatic care in pediatric hospital context; identifying interventions and strategies promoting atraumatic care implemented by Specialist Nurses; identifying the obstacles to the implementation of atraumatic care in practice mentioned by Specialist Nurses. Method: Descriptive, exploratory study of qualitative nature, using focus group, with a convenience sample of eight Specialist Nurses in Child and Pediatric Health, and analyzing the data according to Bardin method. Results: From the analysis of data related to the four pre-established dimensions for the study, 12 categories emerged. Conclusion: Specialist Nurses recognize the importance of atraumatic care in Pediatrics, implementing them intrinsically in practice. The main obstacles to its implementation are the lack of time and resources. They recognize the need for the management of human and material resources, the importance of professional qualification in this subject, and the need to create protocoled interventions related to atraumatic care, in order to promote the humanization of care.